Resultados y retos del proceso de descentralización fiscal en los municipios con presencia de las FARC (2017)
This document analyzes the results of the decentralization process of recent years in the progress or regression of indicators of access to social services such as coverage in education, health and water and sewerage in municipalities where the FARC guerrillas Has exerted territorial influence, having as a point of comparison those territorial entities that have lived with less intensity the Internal Armed Conflict. It is found that those areas where the conflict has been most intense have greater deficiencies in the provision of public goods, so the post-conflict period is seen as an opportunity to close the gaps between these areas and the rest of the country. To this end, the challenges and challenges faced by the Colombian State in occupying territories abandoned by the FARC are identified, with an emphasis on the way in which resources should be directed to the former conflict zones. Comparison of mechanisms related to fiscal decentralization through the use of fixed effects on the available coverage data of the education, health, aqueduct and sewer services.